2001
DOI: 10.1016/s0969-2126(01)00636-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Development of Anticancer Drugs

Abstract: The structures show that compounds can bind to QR1 in more than one orientation. Surprisingly, the two aziridinylindolequinones bind to the enzyme in different orientations. The results presented here reveal two new factors that must be taken into account in the design of prodrugs targeted for activation by QR1: the enzyme binding site is highly plastic and changes to accommodate binding of different substrates, and homologous drugs with different substituents may bind to QR1 in different orientations. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…When comparing the quinone propionic acids (R 2 –R 4 = CH 3 ) with increasing size of the substituent at R 1 (H < CH 3 < CH 3 O), the K m increases, as expected for steric interactions between the quinone ring and the hNQO1 binding motif that result in an unfavorable alignment and position of the quinone ring in the active site. 35 Interestingly, V max decreases with increased size of R 1 substituent on the quinone propionic acid ring. This is quite evident when comparing the Q H -COOH, Q MeO -COOH, and Q Me -COOH species, as the V max of the hydrogen variant (83 µmol·min −1 ·mg −1 ) is roughly two times greater than that of the methyl-substituted quinone propionic acid (38 µmol·min −1 ·mg −1 ) and the methoxy derivative (42 µmol·min −1 ·mg −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the quinone propionic acids (R 2 –R 4 = CH 3 ) with increasing size of the substituent at R 1 (H < CH 3 < CH 3 O), the K m increases, as expected for steric interactions between the quinone ring and the hNQO1 binding motif that result in an unfavorable alignment and position of the quinone ring in the active site. 35 Interestingly, V max decreases with increased size of R 1 substituent on the quinone propionic acid ring. This is quite evident when comparing the Q H -COOH, Q MeO -COOH, and Q Me -COOH species, as the V max of the hydrogen variant (83 µmol·min −1 ·mg −1 ) is roughly two times greater than that of the methyl-substituted quinone propionic acid (38 µmol·min −1 ·mg −1 ) and the methoxy derivative (42 µmol·min −1 ·mg −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there exists a good number of reports on structure-relationship activity 49–56 and docking studies of NQO1 inhibitors and substrates for anticancer therapy, 14, 35, 5762 there is only one published report that provides Michaelis constant ( K m ) and maximum velocity ( V max ) values for the interaction of human NAD(P)H:quinone oxidoreductase-1 with a simple quinone. 44 In addition, the significant differences in reactivity of human NQO1 and rat NQO1 with specific quinone species 63–65 suggest limited applicability of structure-reactivity relationship predictions based on rat NQO1.…”
mentioning
confidence: 99%
“…This implies that ligand dynamics is likely involved in the mechanism of partial NR agonism. In terms of non-NR proteins, differences in binding modes for similar compounds have been noted (Teague, 2003) in crystal structures of transthyretin (Faig et al, 2001) and NAD(P)H:Quinone Oxidoreductase 1 (Faig et al, 2001), where similar ligands also display flipped binding modes. Technologically related to our work, a ligand-detected NMR study revealed that a single ligand can have multiple binding modes when bound to riboflavin synthase, whereas another ligand that binds the same protein has only one binding mode (Scheuring et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For docking purposes, the crystallographic coordinates of the human NQO1 complex with 3-(hydroxymethyl)-5-(2-methylaziridin-1-yl)-1-methyl-2-phenylindole-4,7-dione ( 25 ) were obtained from the Brookhaven Database (PDB code 1H69 33 and resolution 1.86Ǻ) and was edited accordingly to provide a monomer of the protein. The protein complex was then minimized within Sybyl 7.3 (Tripos Ltd., St Louis) while holding all heavy atoms stationary.…”
Section: Methodsmentioning
confidence: 99%